PENERAPAN E-LEARNING DALAM PENGAJARAN DI ERA DIGITALISASI - Yumesri Yumesri; Rusmini; Ahmad Syukri (Jurnal Genta Mulia, 2024)
transformation process into digital form, both contents (contents) and the system. Nowadays the concept of e-Learning has been widely accepted by the world community, as evidenced by the widespread implementation of e-learning in educational institutions. E-learning enables learners to access information that is accurate and up-todate without the barriers of space and time. Ease of access to E-learning makes students can learn from anywhere and at any time origin have adequate internet connection. The conclusion is: (1) Students can easily take courses anywhere without being confined again to the constraints of the institution and the state, (2) Students can easily sit and discuss with experts or experts in the field of interest, (3) Course materials even can easily be taken in various parts of the world without depending on the college in which students learn.